2013
DOI: 10.1021/es402473c
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Ages and Mixing in the Piceance Basin Natural Gas Province, Colorado

Abstract: Reliably identifying the effects of energy development on groundwater quality can be difficult because baseline assessments of water quality completed before the onset of energy development are rare and because interactions between hydrocarbon reservoirs and aquifers can be complex, involving both natural and human processes. Groundwater age and mixing data can strengthen interpretations of monitoring data from those areas by providing better understanding of the groundwater flow systems. Chemical, isotopic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that old groundwater ages can be indicators of slow groundwater velocities. , A study in the EF area reported groundwater velocities on the order of 1–3 m/year in parts of an aquifer containing groundwater >5000 years old, suggesting any benzene releases into old groundwater from leaking UOG wells might have only traveled short distances in the eight years since UOG production commenced. The closest UOG well to an EF water well with a benzene detection was 1.26 km away (SI Table S2), suggesting the benzene detections probably were not from UOG wells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that old groundwater ages can be indicators of slow groundwater velocities. , A study in the EF area reported groundwater velocities on the order of 1–3 m/year in parts of an aquifer containing groundwater >5000 years old, suggesting any benzene releases into old groundwater from leaking UOG wells might have only traveled short distances in the eight years since UOG production commenced. The closest UOG well to an EF water well with a benzene detection was 1.26 km away (SI Table S2), suggesting the benzene detections probably were not from UOG wells.…”
Section: Resultsmentioning
confidence: 99%
“…Groundwater samples from the upper Fort Union Formation mostly contained low concentrations of dissolved oxygen and nitrate and relatively high concentrations of manganese, iron, and sulfate (Figure and Table S1). Eighty percent of the samples contained <0.5 mg/L dissolved oxygen and are characterized as anoxic or suboxic according to the redox framework of McMahon and Chapelle (). Most of the anoxic samples appear to be manganese, iron, and (or) sulfate reducing on the basis of that framework.…”
Section: Resultsmentioning
confidence: 99%
“…These include the relative importance of site‐specific, borehole‐ scale problems due to casing breaks at abstraction well sites (I. Choudhury et al, ) and aquifer‐scale vulnerabilities (Hoque et al, ) to contamination from shallow groundwater and the long‐term impacts of intensive pumping at depth (Khan et al, ; Knappett et al, ; Michael & Khan, ; Zahid et al, ). The presence of modern tracers (e.g., tritium and chlorofluorocarbons (CFCs)) in deeper groundwater systems (typically >150 m) has been attributed to deep pumping in the BAS and in many other aquifer systems globally (Jasechko et al, ; Lapworth et al, ; McMahon et al, ; Samborska et al, ) yet considerable uncertainty remains about the scale and nature of this pumping‐induced contamination. Here we present new evidence from multiple tracers drawn from dedicated, depth‐specific piezometers and actively pumped wells in the BAS, the world's largest deltaic aquifer system, to assess pumping‐induced recharge processes within the deep fresh BAS.…”
Section: Introductionmentioning
confidence: 99%